Islam, Culture, and Social Media: A Study on the Culture of the Social Media Usage in the Covid-19 Pandemic Era - Moh. Huda; Iffatin Nur (The Journal of Society and Media, 2021)
The Covid-19 pandemic has brought various significant impacts on the cultural shift in the society, one of which is the culture of using social media. This is based on the fact that in the Covid-19 pandemic situation there has been a very significant cultural shift in the use of social media, so that in practice, social media culture in the Covid-19 pandemic era has various impacts, both positive and negative impacts. With these various problems, this study aims to look at social media culture in the era of the Covid-19 pandemic from an Islamic perspective. As an effort to answer the problems above, this study uses a literature review with data sources from books, journal articles, and various online newspapers with data analysis methods using content analysis. The findings in this study indicate that the culture of society in the use of social media in the era of the Covid-19 pandemic has experienced a very significant increase. This increase in the view of Islam is supported when humans explore the ability to increase their knowledge and abilities in their fields. On the other hand, if the increasing culture of social media in the era of the Covid-19 pandemic leads people to a crime, then Islam has the consequence of giving a ban.